Ultrasensitive biosensing meta-garment via wetting gradient effect for heat-exhaustion warning - Ming Li; Ganghua Li; Zengqing Li; Yalin Tang; Ruidong Xu; Tong Xu; Yiwen Wang; Yuanyuan Liu; Lijun Qu; Binghao Wang; Yingkui Yang; Mingwei Tian (npj Flexible Electronics)
Abstract Heat exhaustion is a prevalent heat-related illness among firefighters, posing a severe threat to life without timely intervention. However, current firefighter garments are limited by their singular functionality and cannot collect or analyze body fluid during rescue missions. Here, we introduce a wetting gradient effect assisted ultrasensitive meta-garment that incorporates multi-signal biomonitoring, offering an early warning system for heat exhaustion risk. This design enables real-time detection of heart rate, pH value, and the concentrations of glucose, sodium, and potassium in sweat. Benefiting from the surface energy difference, gradient wettability surfaces can be formed, allowing for precise point-to-point fluid control and regulation. Thus, the biosensing fibers require the lowest detection volume (0.1 μL) and fastest response time (1.4 s) reported to date. This innovative garment provides a practical solution for early health warning based on abnormal multi-biomarker changes, representing a significant advancement in firefighter safety.